Synthesis of Fmoc- and Boc-Protected (2S,5S)- and (2R,5R)-5-Aminomethylprolines - Bartuschat, Amelie L.; Hegmann, Nina; Heinrich, Markus R. (Synthesis, 2019)
The proline derivatives (2S,5S)dmamPro, (2S,5S)N-Boc-amPro and (2R,5R)dmamPro are useful building blocks for peptides since they allow conformational fixation of peptidyl–CO–N-prolyl bonds in the unusual cis conformation. The stereoselective syntheses of these dimethylaminomethyl-prolines is achieved from literature-known precursors with overall yields of 23% [over 8 steps for (2S,5S)dmamPro], 33% [over 9 steps for (2S,5S)N-Boc-amPro] and 12% [over 8 steps for (2R,5R)dmamPro]. The applicability of (2S,5S)N-Boc-amPro in peptide synthesis is demonstrated through the preparation of an Fmoc-Val-amPro-OMe dipeptide.
Keywords: proline; conformation; switchable; amides; peptides